Utilización de probióticos para pollos de engorde - Romero Villamagua, Tatiana Elizabeth (2006)
One carries out a field study to analyse the probioticos use in chickens of it puts on weight in the facilities of the Ability of Agricultural Sciences. This had beginning December 2 the 2005 and I conclude January 12 the 2006. The objective of the work was to evaluate the biological and economic answer of the probioticos use in diets for chickens of it puts on weight. The analysed treatments, they were applied during the days that I last the investigation. Of the present study you concludes that the treatments didn't have statistical differences in the total bacterial load